The Early years handbook for students and practitioners an essential guide for the foundation degree and levels 4 and 5 - Hayes, Carol (London Routledge, 2023)
"The Early Years Handbook for Students and Practitioners is a comprehensive and accessible course text for all degree level students undertaking programmes related to early years and childhood studies. Designed and written by the SEFDEY Professional Association and a team of new expert contributors, this text provides a balanced approach to the subjects discussed and encourages you to consider and challenge perceptions of early years and to promote good professional practice. This edition has been extended to cover the learning and development of children from birth to 8 years and features new chapters on research, risk, neuroscience, the environment and more. Divided into four parts - The Student-Practitioner-Professional; The Learning and Development of Children 0-8; The Child, Family and Society; and The Senior Practitioner-Professional - the book covers all aspects of working with young children and engages you with theory that is explicitly linked to your practice. In each chapter, the book seeks to help you develop your professional identity and includes: - Activities to help you to reflect on your own practice - Debates and Dilemmas to promote discussion between students and colleagues - Real-life case studies and photographs to illustrate key points - Extended Reflective Thinking boxes outlining key research in the field and implications for practice. - Suggestions for key projects to help those looking for research topics The book is supported by a companion website featuring, for students, links to useful websites and video material, and an interactive flashcard glossary. Online support for lecturers includes ideas for tasks and activities to use in class and the diagrams and images in the book available to download"
Includes bibliographical references and index.
Keywords: Early childhood educators -- Training of -- Great Britain; Early childhood teachers -- In-service training -- Great Britain; University extension -- Great Britain; Education, Cooperative -- Great Britain; Continuing education -- Great Britain